2017
DOI: 10.1016/j.tics.2017.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Consequences of Impaired Synaptic Plasticity in Schizophrenia through Development: An Integrative Model for Diverse Clinical Features

Abstract: Schizophrenia is associated with alterations in sensory, motor, and cognitive functions that emerge prior to psychosis-onset; identifying pathogenic processes that can account for this multi-faceted phenotype remains a challenge. Accumulating evidence suggests that synaptic plasticity is impaired in schizophrenia. Given the role of synaptic plasticity in learning, memory, and neural circuit maturation, impaired plasticity may underlie many features of the schizophrenia syndrome. Here, we summarize the neurobio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
98
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(108 citation statements)
references
References 223 publications
9
98
1
Order By: Relevance
“…Deficits in one region can propagate as signaling deficits across the network, resulting in abnormal network function. One of the most consistent findings in schizophrenia is a deficit in hippocampal signaling, including increased glutamatergic signaling (13; 64), decreased GABAergic inhibitory control (13; 6567), and impaired neural plasticity (68). Structural and functional deficits in cortico-hippocampal pathways have also been repeatedly demonstrated in schizophrenia patients (79; 15), supporting a dysconnectivity hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Deficits in one region can propagate as signaling deficits across the network, resulting in abnormal network function. One of the most consistent findings in schizophrenia is a deficit in hippocampal signaling, including increased glutamatergic signaling (13; 64), decreased GABAergic inhibitory control (13; 6567), and impaired neural plasticity (68). Structural and functional deficits in cortico-hippocampal pathways have also been repeatedly demonstrated in schizophrenia patients (79; 15), supporting a dysconnectivity hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…The authors proposed that synaptic actin dysfunction may be the convergent mechanism of various psychiatric disorders. NMDA receptor signalling influences the reorganisation of cytoskeleton (Forsyth and Lewis, 2017). Microtubule dysfunction has been previously reported in SZ and other psychiatric disorders (Gardiner, 2017;Marchisella et al, 2016).…”
Section: Discussionmentioning
confidence: 93%
“…Cytoskeleton in brain is involved in development, maintenance and regeneration of neurons (see review (Yan et al, 2016)). It is also involved in spine development, receptor anchoring and trafficking, trans-synaptic adhesion and structural plasticity during long term potentiation and depression (Forsyth and Lewis, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence also suggests that the asymptotic strength of learning-adjusted cortico-striatal connections is higher at the DLS pole 1 than at the VMS pole under normal physiological conditions. For example, more spines create more sites for synaptic contacts, and higher learned synaptic weights (Araya, 2014;Araya et al, 2014;Mancuso et al, 2014;Forsyth & Lewis, 2017). Some have reported that striatal MSPNs' (medium spiny projection neurons') spine densities (cf.…”
Section: Evidence For Faster Learning In Ventro-medial Than Dorso-latmentioning
confidence: 99%